Sero-surveillance of peste des petits ruminant viral antibody in goats at different areas of Bangladesh - Yousuf, Md Abu; Rahman, Md Mostafizur; Alauddin, Md; Rahman, SM Badier; Islam, SM Shariful; Islam, Md Rafiqul; Ershaduzzaman, Md (Asian Journal of Medical and Biological Research, 2017)
Peste des petits ruminants (PPR) is a devastating and killer disease of domesticated small ruminants particularly goats. The present study was conducted on the serosurveillance of PPR in goats in different areas of Bangladesh. Blood samples were collected apparently from different years of age of goats in different areas of Bangladesh. All sera were subjected to serological test by competitive ELISA. For sero-surveillance of PPR virus total 200 serum samples were collected at different areas of Bangladesh such as Bogra18/60 (30%), Sirajganj 26/30 (86.67%), Mymensingh 5/50 (10%) and Rangpur 7/60 (11.67%). Among those 56 were seropositive and 144 were seronegative. The mean positive antibody titer ±SD of goat serum samples was 26.03 and the mean negative antibody titer was 77.76 The highest antibodies was detected in Sirajganj that was vaccinated flock whereas the lowest antibodies was found Mymensingh that was non vaccinated goat. It may be concluded that, in absence of vaccination, the presence of PPRV antibodies indicated that PPR viruses were circulating among the goats population but the vaccinated goat’s have protective level of antibodies against PPRV. So that preventive measures should be taken in goats against PPR virus by vaccination with proper maintain of cool chain. Asian J. Med. Biol. Res. September 2017, 3(3): 347-351